Pengembangan E-LKPD Berbasis Flipbook Interaktif untuk Meningkatkan Motivasi Belajar Siswa pada Materi Hidrokarbon - Agnes Aurelia Silalahi; Marudut Sinaga (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Hydrocarbon material is one of the chemical materials that has a high level of abstraction, so it often causes learning difficulties in students, especially in understanding molecular structure, compound nomenclature, and the concept of isomerism. These difficulties have an impact on low student learning motivation in chemistry learning. This study aims to develop an interactive flipbook-based E-LKPD on hydrocarbon material, and analyze its validity, practicality, and effectiveness in increasing student learning motivation. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 37 students of grade XI IPA SMA Santo Yoseph, Medan. The research instruments included validation sheets from material experts and media experts, practicality questionnaires, learning motivation questionnaires, and learning outcome tests. The validation results showed an average score of 3.75 for material experts and 3.80 for media experts, which is included in the very valid category. The practicality results obtained a percentage of 88% with a very practical category. Student learning motivation increased from an average score of 65.2 to 82.7 after using an interactive flipbook-based e-LKPD. These results indicate that the developed e-LKPD is highly valid, practical, and effective in increasing student learning motivation in hydrocarbons.